2020
DOI: 10.1002/ecy.2983
|View full text |Cite
|
Sign up to set email alerts
|

Rapid recovery of ecosystem function following extreme drought in a South African savanna grassland

Abstract: Climatic extremes, such as severe drought, are expected to increase in frequency and magnitude with climate change. Thus, identifying mechanisms of resilience is critical to predicting the vulnerability of ecosystems. An exceptional drought ( Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
60
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 42 publications
6
60
0
Order By: Relevance
“…Alternatively, this effect may not be in terms of vegetation composition in systems where the dominant species rely less on a persistent seed bank (Gibson, 2009). But, the high abundance of annual species in the seed bank might play an important role in ecosystem functioning after the dry period is over (e.g., Wilcox et al, 2020). These species develop rapidly and can cover and protect the soil, and create favorable niches facilitating the recruitment of perennial species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, this effect may not be in terms of vegetation composition in systems where the dominant species rely less on a persistent seed bank (Gibson, 2009). But, the high abundance of annual species in the seed bank might play an important role in ecosystem functioning after the dry period is over (e.g., Wilcox et al, 2020). These species develop rapidly and can cover and protect the soil, and create favorable niches facilitating the recruitment of perennial species.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in rainfall event size and lengthening the time between rain events may have several impacts on community composition and diversity (Knapp et al, 2002;Miranda et al, 2009;Talmon et al, 2011). In grassland ecosystems, droughts can rapidly alter plant community composition (Fynn & O'Connor, 2000) and ecosystem functioning (Wilcox et al, 2020). Drought can decrease the abundance of dominant perennial grasses (Báez et al, 2013), and increase the abundance of annual and perennial forbs during the drought and after it ends (Milton & Dean, 2000;Hodgkinson & Müller, 2005;Porensky et al, 2013;O'Connor, 2015;Munson et al, 2016;Swemmer et al, 2018).…”
mentioning
confidence: 99%
“…However, other studies have reported nonsignificant effects of N addition on post-drought recovery (Tilman 1996 because N addition was associated with stronger responses by plant shoots, such as mortality or wilting, during drought periods (Southon et al 2012) offsetting the positive effects of N addition on post-drought recovery. Wilcox et al (2020) suggested that compensation plays a critical role in ecosystem resilience to extreme drought in savanna grasslands, and thus long-term N addition will negatively impact recovery if diversity or compensation are reduced. Hence, we still do not have a clear understanding of the effects of N FIG.…”
Section: Introductionmentioning
confidence: 99%
“…Wilcox et al. (2020) suggested that compensation plays a critical role in ecosystem resilience to extreme drought in savanna grasslands, and thus long‐term N addition will negatively impact recovery if diversity or compensation are reduced. Hence, we still do not have a clear understanding of the effects of N addition on grassland recovery immediately after drought events or at longer time scales.…”
Section: Introductionmentioning
confidence: 99%
“…In grasslands, drought can alter community composition and structure, decrease aboveground net primary productivity (ANPP), and shift biomass allocation patterns (Frank 2007;Evans et al 2011;Hoover et al 2014;Meng et al 2019;Zhang et al 2019;Zhao et al 2020); however, grasslands are also highly resilient ecosystems. Previous studies suggested that ANPP can completely recover to pre-drought levels within one year after drought (Hoover et al 2014;Wilcox et al 2020). While legacy effects of drought are often negative (Sala et al 2012), some grasslands are more productive than expected one year after drought (Gri n- Nolan et al 2018).…”
Section: Introductionmentioning
confidence: 99%